An Introduction to communication - Turner, Lynn H.; West, Richard (Cambridge, United Kingdom : Cambridge University Press, 2019)
Prioritizing brevity and clarity, this textbook introduces the study of communication through examples and applications of communication in a variety of contexts. With a unique focus on diversity and the impact of culture, each chapter opens with a case study that identifies a communication challenge, which the chapter addresses throughout, and concludes with questions that respond to that challenge. A consistent, organized structure with numerous features including fundamental issues, questions for understanding and analysis, theoretical insight (examining a particular relevant theory), and a skill set section, easily guides you through the foundations of the study of communication. Cross-referencing between chapters demonstrates the multidimensional nature of communication and the everyday talk sections demonstrate how each topic relates to technology, the workplace, or health issues. Offering a wealth of diverse examples from students' personal, professional, and online lives, this book teaches skills allowing students from all academic backgrounds to understand communication.
Machine generated contents note: pt. I Communication Foundations -- 1.The Communication Process -- Chapter Outline -- Chapter Goals -- Communication Encounter: Sofia Contedaras -- Background -- Definition of Terms -- Communication and Intentionality -- Four Communication Models -- Historical Foundations of the Field -- Fundamental Issues -- The Destructive Side of Communication -- Ethical Systems of Communication -- Communication Response: Sofia Contedaras -- Questions for Understanding -- Questions for Analysis -- Suggestions for Further Reading -- 2.Culture and Communication -- Chapter Outline -- Chapter Goals -- Communication Encounter: Dora Ellison and Augustina Riverton -- Background -- Cultural Diversity in the USA -- Defining and Interpreting Culture -- Assumptions about Culture -- Imperatives for Studying Culture and Communication -- Fundamental Issues -- Dimensions of National Culture -- Challenges and Barriers to Intercultural Communication Note continued: Theoretical Insight: Co-Cultural Theory (Orbe) -- Enhancing Your Skills -- Applying Working Toward Commonality at Work -- Applying Working Toward Commonality in the Family -- Communication Response: Dora Ellison and Augustina Riverton -- Questions for Understanding -- Questions for Analysis -- Suggestions for Further Reading -- 3.Perception, the Self, and Communication -- Chapter Outline -- Chapter Goals -- Communication Encounter: Greta Brigham and Jackson Wilmont -- Background -- The Process of Perception -- Influences on Perception -- Fundamental Issues -- Biases Affecting Perception -- The Self and Impression Management -- Theoretical Insight: Attribution Theory (Kelley) -- Enhancing Your Skills -- Applying Perception Checking at Work -- Applying Perception Checking with Friends -- Communication Response: Greta Brigham and Jackson Wilmont -- Questions for Understanding -- Questions for Analysis -- Suggestions for Further Reading Note continued: 4.Verbal and Nonverbal Communication -- Chapter Outline -- Chapter Goals -- Communication Encounter: Nadine Hellman and Randy Mitchell -- Background -- Interpreting Verbal Communication -- Interpreting Nonverbal Communication -- The Relationship between Verbal and Nonverbal Communication -- Fundamental Issues in Verbal Communication -- Characteristics of Verbal Codes -- Influences on Verbal Communication -- Problematic Aspects of Verbal Communication -- Theoretical Insight: Linguistic Determinism/Relativity Theory (Sapir & Whorf) -- Fundamental Issues in Nonverbal Communication -- Types of Nonverbal Codes -- Influences on Nonverbal Communication -- Theoretical Insight: Expectancy Violations Theory (Burgoon) -- Enhancing Your Skills -- Applying Owning Your Opinions at Work -- Applying Owning Your Opinions with Friends -- Communication Response: Nadine Hellman and Randy Mitchell -- Questions for Understanding -- Questions for Analysis Note continued: Suggestions for Further Reading -- 5.Listening and Responding -- Chapter Outline -- Chapter Goals -- Communication Encounter: Professor Nash and Rodney Jasper -- Background -- The Importance of Listening -- Differentiating between Hearing and Listening -- Components of the Listening Process -- Fundamental Issues -- Personal and Preferred Listening Styles -- Poor Listening Habits -- Influences on Listening: Technology and Culture -- Theoretical Insight: Working Memory Theory (Baddeley) -- Enhancing Your Skills -- Applying Listening with Empathy in the Family -- Communication Response: Professor Nash and Rodney Jasper -- Questions for Understanding -- Questions for Analysis -- Suggestions for Further Reading -- pt. II Communication Types and Contexts -- 6.Interpersonal and Relational Communication -- Chapter Outline -- Chapter Goals -- Communication Encounter: Marsha and Tami Neimann -- Background -- Definitions Note continued: Distinguishing between Interpersonal and Relational Communication -- Fundamental Issues -- Relationship Development -- Communication Behaviors Characterizing Close Relationships -- Technology and Relational Communication -- Theoretical Insight: Relational Dialectics Theory (Baxter) -- Enhancing Your Skills -- Applying Descriptive Communication at Work -- Applying Descriptive Communication in the Family -- Communication Response: Marsha and Tami Neimann -- Questions for Understanding -- Questions for Analysis -- Suggestions for Further Reading -- 7.Communication in Small Groups and Organizations -- Chapter Outline -- Chapter Goals -- Communication Encounter: Norris Wright and Faye Reynolds -- Background -- Interpreting Small Groups and Organizations -- Communication in Small Groups and Organizations -- Fundamental Issues in Small Group Communication -- Group Roles -- Group Decision Making and Problem Solving -- Theoretical Insight: Groupthink (Janis) Note continued: Fundamental Issues in Organizational Communication -- Leadership -- Managing Work-Home Issues -- Theoretical Insight: Theory of Organizational Culture (Pacanowsky & O'Donnell-Trujillo) -- Enhancing Your Skills -- Applying Openness to Feedback in the Organization -- Applying Openness to Feedback in a Small Group -- Communication Response: Norris Wright and Faye Reynolds -- Questions for Understanding -- Questions for Analysis -- Suggestions for Further Reading -- 8.Social/Mass Media and Communication -- Chapter Outline -- Chapter Goals -- Communication Encounter: Beth Wilder and Chao Li -- Background: The Importance of Media in Everyday Life -- Fundamental Issues in Mass Media -- Interpreting Mass Media -- History of Mass Media -- Media Representations -- Theoretical Insight in Mass Media: Agenda-Setting Theory (McCombs & Shaw) -- Fundamental Issues in Social Media -- Interpreting and Understanding Social Media -- The Effects of Social Media Note continued: Theoretical Insight in Social Media: Social Information Processing Theory (Walther) -- Enhancing Your Skills -- Developing Media Literacy as a Media Consumer -- Applying Civil Discourse Online -- Communication Response: Beth Wilder and Chao Li -- Questions for Understanding -- Questions for Analysis -- Suggestions for Further Reading -- 9.Preparing and Composing Your Speech -- Chapter Outline -- Chapter Goals -- Communication Encounter: Victoria Bruno -- Background -- Aristotle: One Philosopher's Major Influence -- Our Presentational Society -- Types of Presentations -- Fundamental Issues -- Selecting and Narrowing a Topic -- Researching and Supporting Your Presentation -- Organizing and Outlining -- Theoretical Insight: The Rhetoric (Aristotle) -- Enhancing Your Skills -- Applying Establishing a Personal Inventory of Speaking with Friends -- Communication Response: Victoria Bruno -- Questions for Understanding -- Questions for Analysis Note continued: Suggestions for Further Reading -- 10.Audience Analysis and Speech Delivery -- Chapter Outline -- Chapter Goals -- Communication Encounter: Dexter Ward -- Background -- The Audience-Speaker Relationship -- Presenting with Substance -- Fundamental Issues -- Audience Analysis -- Communication Apprehension -- Technology -- Delivering a Presentation -- Delivery Formats -- Delivery Components -- Theoretical Insight: Contagion Theory (Nuttin) -- Enhancing Your Skills -- Applying Sustaining Professionalism at Work -- Communication Response: Dexter Ward -- Questions for Understanding -- Questions for Analysis -- Suggestions for Further Reading.
Includes bibliographical references and index.
Keywords: COMMUNICATION